1 (** {1 Kleene Algebra Definition and Relational Kleene Algebra }
3 Author: Quentin Garchery (Université Paris-Saclay)
16 clone export algebra.CommutativeMonoid with type t = t, constant unit = zero,
17 function op = (+), axiom .
19 clone algebra.Monoid with type t = t, constant unit = one,
20 function op = (*), axiom .
22 axiom Mul_zero_l : forall x. zero * x = zero
23 axiom Mul_zero_r : forall x. x * zero = zero
25 axiom Mul_distr_l : forall x y z : t. x * (y + z) = x * y + x * z
26 axiom Mul_distr_r : forall x y z : t. (y + z) * x = y * x + z * x
28 let rec ghost function (^) (x : t) (n : int) : t
32 if n = 0 then pure{one} else let r = x ^ (n-1) in pure {x * r}
34 clone int.Exponentiation with type t = t, constant one = one,
35 function (*) = (*), function power = (^), lemma .
41 clone export SemiRing with axiom .
43 axiom Idem : forall x : t. x + x = x
45 predicate (<=) (x : t) (y : t) = x + y = y
47 lemma le_refl : forall x. x <= x
49 lemma le_antisym : forall x y. x <= y -> y <= x -> x = y
51 lemma le_trans : forall x y z. x <= y -> y <= z -> x <= z
53 lemma zero_le : forall x. zero <= x
55 lemma le_compat_add : forall x y z. x <= y -> x + z <= y + z
57 lemma le_add : forall x y. x <= x + y
59 lemma le_add_le : forall x y z. x <= z -> y <= z -> x + y <= z
61 lemma add_le : forall x y z. x + y <= z -> x <= z
63 lemma le_compat_add_left : forall x y z. x <= y -> z * x <= z * y
65 lemma le_compat_add_right : forall x y z. x <= y -> x * z <= y * z
73 clone export Dioid with axiom .
75 (* We denote x^* as !x *)
78 axiom Star_unfold_left : forall x. one + x * !x <= !x
80 axiom Star_unfold_right : forall x. one + !x * x <= !x
82 axiom Star_induct_left : forall x y z. z + x * y <= y -> !x * z <= y
84 axiom Star_induct_right : forall x y z. z + y * x <= y -> z * !x <= y
86 lemma one_le_star : forall x. one <= !x
88 lemma mul_var_le_star : forall x. x * !x <= !x
90 lemma var_mul_le_star : forall x. !x * x <= !x
92 lemma power_le_star : forall i x. i >= 0 -> x ^ i <= !x
94 lemma star_mul_star : forall x. !x * !x = !x
97 lemma star_star : forall x. !(!x) = !x
99 lemma star_unfold_left : forall x. one + x * !x = !x
100 by one + x * (one + x * !x) <= one + x * !x
102 lemma star_unfold_right : forall x. one + !x * x = !x
103 by one + (one + !x * x) * x <= one + !x * x
105 lemma star_le : forall x y. x <= y -> !x <= !y
106 by one + x * !y <= !y
108 lemma le_star_left_right : forall x y z. z * x <= y * z -> z * !x <= !y * z
109 by z + (!y * z) * x <= !y * z
111 lemma le_star_right_left : forall x y z. x * z <= z * y -> !x * z <= z * !y
112 by z + x * (z * !y) <= z * !y
114 lemma slide_left : forall x y. !(x + y) = !x * !(y * !x)
116 so y * !x <= !(x + y)
117 so !(y * !x) <= !(!(x + y)) <= !(x + y)
118 so !x * !(y * !x) <= !(x + y)
119 so one + (x + y) * (!x * !(y * !x)) <= !x * !(y * !x)
120 so !(x + y) <= !x * !(y * !x)
122 lemma slide_right : forall x y. !(x + y) = !(!x * y) * !x
124 so !x * y <= !(x + y)
125 so !(!x * y) <= !(!(x + y)) <= !(x + y)
126 so !(!x * y) * !x <= !(x + y)
127 so one + (!(!x * y) * !x) * (x + y) <= !(!x * y) * !x
128 so !(x + y) <= !(!x * y) * !x
130 (** Conway's equality: a way to cut x^* in slices of size x^n *)
132 let rec ghost function sum_pow (x : t) (a b: int) : t
133 requires { b >= a >= 0 }
135 = if b = a then pure{zero} else
136 let m1 = sum_pow x a (b - 1) in
137 let m2 = x ^ (b - 1) in
140 lemma sum_pow_left: forall x a b.
142 sum_pow x a b = x^a + sum_pow x (Int.(+) a 1) b
144 lemma mul_sum_pow: forall x a b.
146 sum_pow x a b * x = sum_pow x (Int.(+) a 1) (Int.(+) b 1)
148 lemma sum_pow_le_star: forall x a b.
152 lemma Conway_equality: forall x n.
154 !x = !(x^n) * sum_pow x 0 n
155 by !(x^n) * sum_pow x 0 n <= !x
156 so !(x^n) * sum_pow x 0 n * x = !(x^n) * sum_pow x 1 n + !(x^n) * x ^ n
157 <= !(x^n) * sum_pow x 0 n
158 so one + !(x^n) * sum_pow x 0 n * x <= !(x^n) * sum_pow x 0 n
168 (* Relational Algebra: sets of pairs of the same type *)
174 (** Specify zero, one, +, * and ! in terms of membership *)
176 constant zero : t = empty
177 lemma zero_def : forall x. not mem x zero
179 constant one : t = map (fun a -> (a, a)) all
180 lemma one_def : forall x : a. mem (x, x) one
182 let ghost function post (s : t) (x : a)
183 ensures { forall y. mem y result <-> mem (x, y) s }
185 map (fun p -> let (_, a2) = p in a2)
186 (filter s (fun p -> let (a1, _) = p in pure{a1 = x}))
188 let ghost function pre (s : t) (y : a)
189 ensures { forall x. mem x result <-> mem (x, y) s }
191 map (fun p -> let (a1, _) = p in a1)
192 (filter s (fun p -> let (_, a2) = p in pure {a2 = y}))
194 let ghost function (+) (s1 s2 : t)
195 ensures { forall x. mem x result <-> mem x s1 \/ mem x s2 }
199 let ghost function (*) (s1 s2 : t)
200 ensures { forall a1 a2. mem (a1, a2) result <->
201 exists x. mem (a1, x) s1 /\ mem (x, a2) s2 }
204 (fun p -> let (a1, a2) = p in
205 not (disjoint (post s1 a1) (pre s2 a2)))
207 lemma unit_l : forall x. one * x = x
210 lemma unit_r : forall x. x * one = x
213 lemma assoc_mul : forall x y z. x * y * z = x * (y * z)
214 by forall e. (mem e (x * y * z) -> mem e (x * (y * z))) /\
215 (mem e (x * (y * z)) -> mem e (x * y * z))
217 clone Dioid with type t = t, constant zero = zero,
218 constant one = one, function (+) = (+), function (*) = (*), lemma .
220 lemma le_mem : forall x y. x <= y <-> forall u. mem u x -> mem u y
222 inductive in_star t (a, a) =
223 | Star_0 : forall x s. in_star s (x, x)
224 | Star_s : forall x y z s. in_star s (x, y) -> mem (y, z) s -> in_star s (x, z)
226 let ghost function (!_) (s : t) =
227 filter all (in_star s)
229 lemma power_in_star : forall s : t, i, p : (a, a).
230 i >= 0 -> mem p (s ^ i) -> mem p !s
231 by i > 0 -> let (x, z) = p in
232 exists y. (in_star s (x, y) by mem (x, y) (s ^ (i-1))) /\ mem (y, z) s
234 lemma star_in_power : forall s x y.
235 in_star s (x, y) -> (exists i. i >= 0 /\ mem (x, y) (s ^ i))
237 lemma star_spec : forall s : t, p : (a, a).
238 mem p !s <-> exists i. i >= 0 /\ mem p (s ^ i)
240 lemma star_unfold_l : forall x u. mem u (one + x * !x) -> mem u !x
241 by mem u (x * !x) -> (exists i. i >= 0 /\ mem u (x * x ^ i))
242 by let (u1, u2) = u in
243 exists v. mem (u1, v) x /\ mem (v, u2) !x
244 so exists i. i >= 0 /\ mem u (x * x ^ i)
246 lemma star_unfold_r : forall x u. mem u (one + !x * x) -> mem u !x
247 by mem u (!x * x) -> (exists i. i >= 0 /\ mem u (x ^ i * x))
248 by let (u1, u2) = u in
249 exists v. mem (u1, v) !x /\ mem (v, u2) x
250 so exists i. i >= 0 /\ mem u (x ^ i * x)
252 lemma star_induct_left_ind : forall x y z i. i >= 0 ->
253 z + x * y <= y -> x^i * z <= y
255 lemma star_induct_left_lem : forall x y z i. i >= 0 ->
256 z + x * y <= y -> forall u. mem u (x^i * z) -> mem u y
258 lemma star_induct_left : forall x y z.
259 z + x * y <= y -> !x * z <= y
260 by forall u. mem u (!x * z) -> (exists i. i >= 0 /\ mem u (x^i * z))
261 by let (u1, u2) = u in
262 exists v. mem (u1, v) !x /\ mem (v, u2) z
263 so exists i. i >= 0 /\ mem u (x^i * z)
265 lemma star_induct_right_ind : forall x y z i. i >= 0 ->
266 z + y * x <= y -> z * x^i <= y
268 lemma star_induct_right_lem : forall x y z i. i >= 0 ->
269 z + y * x <= y -> forall u. mem u (z * x^i) -> mem u y
271 lemma star_induct_right : forall x y z.
272 z + y * x <= y -> z * !x <= y
273 by forall u. mem u (z * !x) -> (exists i. i >= 0 /\ mem u (z * x^i))
274 by let (u1, u2) = u in
275 exists v. mem (u1, v) z /\ mem (v, u2) !x
276 so exists i. i >= 0 /\ mem u (z * x^i)
278 (** Prove that this forms a Kleene Algebra *)
280 clone KleeneAlgebra with type t = t, constant zero = zero,
281 constant one = one, function (+) = (+), function (*) = (*),
282 function (!_) = (!_), lemma .